2010
DOI: 10.1111/j.1399-3038.2010.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

The most important contact sensitizers in Polish children and adolescents with atopy and chronic recurrent eczema as detected with the extended European Baseline Series

Abstract: The differential diagnostic work-up of children with chronic eczema should involve patch testing, also in cases with confirmed atopy. In our previous study, contact allergy was detected in every second child with chronic eczema. The aim of the present study was to identify the most important sensitizers in atopic children with eczema. During an allergy screening program, 103 consecutive children aged 7-8 and 93 adolescents aged 16-17 were enrolled. The inclusion criterion was chronic recurrent eczema as detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 25 publications
1
49
0
5
Order By: Relevance
“…On the other hand, after withdrawal of this preservative from most consumer products, vaccines seem now the major source of thiomersal exposure with little everyday exposure that would give the chance to assess the clinical relevance of the sensitization. In a recent study of Polish children and adolescents with chronic or recurrent eczema, positive patch test to thiomersal was found in 11.7% of children (7-8 years of age) and 37.6% of adolescents (16-17 years of age) [64]. These differences reflect changing exposure patterns: the adolescents have received six thiomersal-preserved vaccines during their life course, with the last immunization taking place 2-3 years before the mentioned study.…”
Section: Immunotherapy Of Allergic Contact Dermatitis Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, after withdrawal of this preservative from most consumer products, vaccines seem now the major source of thiomersal exposure with little everyday exposure that would give the chance to assess the clinical relevance of the sensitization. In a recent study of Polish children and adolescents with chronic or recurrent eczema, positive patch test to thiomersal was found in 11.7% of children (7-8 years of age) and 37.6% of adolescents (16-17 years of age) [64]. These differences reflect changing exposure patterns: the adolescents have received six thiomersal-preserved vaccines during their life course, with the last immunization taking place 2-3 years before the mentioned study.…”
Section: Immunotherapy Of Allergic Contact Dermatitis Reviewmentioning
confidence: 93%
“…Among 45 patients with positive patch tests to thiomersal who were challenged with subcutaneous administration of this hapten, one patient developed generalized eczema and four reacted with local eczematous reaction; nevertheless, 40 patch test-positive patients remained tolerant to subcutaneous injection of the hapten [66]. On the other hand, there are data indicating a higher frequency of contact hypersensitivity to thiomersal among patients with chronic eczema: when comparing the aforementioned positivity rates among Polish children and adolescents with chronic eczema (11.7% in 7-8-year-olds and 37.6% in 16-17-year-olds in 2009 [64]) with samples from the general Polish population (8% among 13-15-year-olds in 1999 [67] and 18.5% among 18-19-yearolds in 2002 [68]), it becomes apparent that despite the partial withdrawal of thiomersalcontaining vaccines that took place between these studies, the sensitization rates among children with eczema are 1.5-2-times higher than in the general population, which would indicate that thiomersal hypersensitivity might be of some importance in ACD. Altogether, the elicitation of clinical ACD to thiomersal seems influenced in some way by a complex and notyet-understood interplay between the primary and present routes of exposure.…”
Section: Immunotherapy Of Allergic Contact Dermatitis Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Almost half of all children with chronic recurrent eczema, who gave affirmative answers to the eczema module in the ISAAC questionnaire and had positive prick test (confirmed atopy), were found to have a reaction to at least 1 hapten on the European Baseline Patch Test Series. 49 A detailed examination of these children revealed that 1 in 3 (and 1 in 2 adolescents) was ultimately diagnosed with allergic contact dermatitis. Notably, a considerable proportion of those with flexural eczema (1 in 5 children and 1 in 2 adolescents) had no symptoms qualifying for the diagnosis of atopic dermatitis.…”
Section: Contact Dermatitis May Play a Role In Atopic Dermatitismentioning
confidence: 99%
“…Allergic reactions may manifest as contact chelitis, contact stomatitis, perioral eczyma, labial edema, oral pain, peeling of lips, and dyspnea. [12]…”
mentioning
confidence: 99%